COVID-19 in patients with autoimmune diseases: characteristics and outcomes in a multinational network of cohorts across three countries. (16th March 2021) - Tan, Eng Hooi; Sena, Anthony G; Prats-Uribe, Albert; You, Seng Chan; Ahmed, Waheed-Ul-Rahman; Kostka, Kristin; Reich, Christian; Duvall, Scott L; Lynch, Kristine E; Matheny, Michael E; Duarte-Salles, Talita; Bertolin, Sergio Fernandez; et al.
Abstract: Objective: Patients with autoimmune diseases were advised to shield to avoid coronavirus disease 2019 (COVID-19), but information on their prognosis is lacking. We characterized 30-day outcomes and mortality after hospitalization with COVID-19 among patients with prevalent autoimmune diseases, and compared outcomes after hospital admissions among similar patients with seasonal influenza. Methods: A multinational network cohort study was conducted using electronic health records data from Columbia University Irving Medical Center [USA, Optum (USA), Department of Veterans Affairs (USA), Information System for Research in Primary Care-Hospitalization Linked Data (Spain) and claims data from IQVIA Open Claims (USA) and Health Insurance and Review Assessment (South Korea). All patients with prevalent autoimmune diseases, diagnosed and/or hospitalized between January and June 2020 with COVID-19, and similar patients hospitalized with influenza in 2017–18 were included. Outcomes were death and complications within 30 days of hospitalization. Results: We studied 133 589 patients diagnosed and 48 418 hospitalized with COVID-19 with prevalent autoimmune diseases. Most patients were female, aged ≥50 years with previous comorbidities. The prevalence of hypertension (45.5–93.2%), chronic kidney disease (14.0–52.7%) and heart disease (29.0–83.8%) was higher in hospitalized vs diagnosed patients with COVID-19. Compared with 70 660 hospitalized with influenza, those admitted with COVID-19 had more respiratory complications including pneumonia and acute respiratory distress syndrome, and higher 30-day mortality (2.2–4.3% vs 6.32–24.6%). Conclusion: Compared with influenza, COVID-19 is a more severe disease, leading to more complications and higher mortality.